Impact of a multicomponent physical exercise program on intrinsic capacity in community-dwelling older adults - Sarah Giulia Felipe; Clarissa Biehl Printes; Douglas Kazutoshi Sato; Rafael Reimann Baptista (PeerJ)
Introduction In 2015, the World Health Organization introduced intrinsic capacity, a health indicator encompassing five domains aimed at promoting healthy aging. Multicomponent exercise programs are recommended to maintain and optimize intrinsic capacity; however, evidence on their effects in robust older adults is limited. This study aimed to evaluate the effects of a multicomponent exercise program on intrinsic capacity in older adults. Methods Older adults (≥60 years) enrolled in a multicomponent training program in Porto Alegre (RS) were evaluated for intrinsic capacity using specific tests for each domain. The total score, ranging from 0 to 10 points, was obtained by summing the scores of the five domains. Participants underwent a 12-week multicomponent exercise intervention and were reassessed. Results After the 12-week intervention, the composite intrinsic capacity score significantly increased. Significant improvements were found in the cognitive, vitality and locomotion domains. The practice of Chinese curative gymnastics contributed to a one-point increase in the composite intrinsic capacity score. No association was found between frequency, duration of training, or the number of exercise modalities and the composite intrinsic capacity score. Conclusion The multicomponent exercise program positively influenced composite intrinsic capacity, with notable improvements in vitality, cognition, and mobility. Personalization and individualization of training, combined with health education and social integration, were crucial in promoting healthy aging in the studied sample.